NILAI TERMOFISIKA DAUN KAPUK, DAUN SIRIH DAN DAUN BUNGA KEMBANG SEPATU SEBAGAI BAHAN KOMPRES DEMAM - Sri Zelviani; Riska Riska; Fitriyanti Fitriyanti (JFT : Jurnal Fisika dan Terapannya, 2020)
Fever was a condition where the body temperature was above 37,5oC. Fever was also part of the immune process that was fighting infections due to viruses, bacteria and parasites. Fever was considered very high and potentially dangerous if the temperature reaches 39oC. This research used experimental of temperature Cobra3 method. The research showed  thermophysical values of kapok leaves, red betel leaves and hibiscus flower leaves as ingredients for fever compresses. The results of kapok leaves were the average specific heat value of 45.07 (J/groC), and heat capacity value of 901.30 (J/oC). For the sample of red betel leaves, the average specific heat value were 72.50 (J/groC) and heat capacity value 1,540 (J/oC). Sample of hibiscus flower leaves were the average specific heat value 96.30 (J/groC) and the heat capacity value 1,925.3 (J/oC).